Long-range regulation at the SOX9 locus in development and disease. Issue 10 (26th May 2009) - Gordon, C T; Tan, T Y; Benko, S; FitzPatrick, D; Lyonnet, S; Farlie, P G
Abstract : The involvement of SOX9 in congenital skeletal malformation was demonstrated 15 years ago with the identification of mutations in and around the gene in patients with campomelic dysplasia (CD). Translocations upstream of the coding sequence suggested that altered expression of SOX9 was capable of severely impacting on skeletal development. Subsequent studies in humans and animal models pointed towards a complex regulatory region controlling SOX9 transcription, involving ∼1 Mb of upstream sequence. Recent data indicate that this regulatory domain may extend substantially further, with identification of several disruptions greater than 1 Mb upstream of SOX9 associated with isolated Pierre Robin sequence (PRS), a craniofacial disorder that is frequently a component of CD. The translocation breakpoints upstream of SOX9 can now be clustered into three groups, with a trend towards less severe skeletal phenotypes as the distance of each cluster from SOX9 increases. In this review we discuss how the identification of novel lesions surrounding SOX9 support the existence of tissue specific enhancers acting over a large distance to regulate expression of the gene during craniofacial development, and we highlight the potential for discovery of additional regulatory elements within the extended SOX9 control region.